The prevalence of hyaline membrane disease and the value of shake test and lamellar body concentration in preterm infants - Dzulfikar DLH; Ali Usman; Melinda D Nataprawira; Aris Primadi (Indonesian Pediatric Society, 2003)
Background The morbidity and mortality of hyaline membrane dis-ease (HMD) are quite high due to delayed diagnosis and intervention.Commonly, HMD occurs in preterm infants with surfactant deficiencybecause of lung immaturity. Lung maturity test could be performedusing biochemical, biophysical, and amniotic fluid turbidity test.Objective To find out HMD prevalence and the value of shaketest and lamellar body concentration in diagnosing HMD in preterminfants.Methods This was a cross-sectional study carried out at HasanSadikin Hospital Bandung on preterm infants born during October-December 2001. The shake test was performed using gastric fluidand amniotic fluid while the lamellar body concentration was per-formed using amniotic fluid.Results During the 3-month period, 571 infants were born, of 64(11.2%) preterm infants, only 41 (64%) fulfilled the inclusion crite-ria; among those preterm infants, 14 (34%) suffered from respira-tory distress and 7 suffered from HMD (prevalence 17%). All HMDcases occurred in infants less than 32 weeks for gestational age.In 7 preterm infants with HMD, the shake test of gastric fluid ob-tained by lavage showed negative results in 3 and +1 in 4 infants;while the shake test of amniotic fluid revealed negative result in 5and +1 in 2 infants. Lamellar body concentration of amniotic fluidwas â‰¤18,000/ml in all HMD infants. Among three infants less than32 weeks for gestational age who did not suffer from HMD, +1shake test of gastric fluid was found in 2 infants and +2 in 1 infant;while shake test of amniotic fluid showed negative result in 1 infantand +1 in 2; the lamellar body concentration of amniotic fluid wasâ‰¤18,000/ml in 2 infants and >18,000/ml in 1 infant.Conclusions We concluded that HMD occurred in 17% of preterminfants. The shake test of gastric and amniotic fluids revealed nega-tive or +1 results whereas lamellar body concentration had valueof less than or equal to 18,000/mL. More extensive studies arewarranted to assess the validity (sensitivity, specificity and predic-tive values) of these measurements